Infrastructural Development in Rural India - Gupta, Amit (Journal of Commerce and Trade, 2013)
The study scrutinizes the infrastructural development in Rural India. The purpose of this paper is to analyze and provide the information regarding the development schemes in rural area. Rural sector which plays an important role in India is still seeking the advancement and development for their present and future. The paper provides the information regarding the development of roads, electricity, transportation and facilities like hospitals, schools etc. The study reveals that the work of development is tougher in rural areas in comparison to urban areas due to many social and physical barriers. Though the progress is very slow but the analysis shows that the actions taken by Indian Government, International Organizations like World Bank and Indian NGO’s would definitely be fruitful and long lasting.